Re-conceptualizing career success: a~contextual approach - Hugh Gunz; Wolfgang Mayrhofer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
Career success has hitherto been conceptualized in ways that make its operationalization difficult to distinguish from other properties of the person, such as job satisfaction or remuneration. We argue that this is because these conventional operationalizations neglect the 'career' dimension of career success. We introduce a perspective on career studies, Social Chronology Theorizing (SCrT), which in our understanding provides a richer view of career success. It calls for contextualization, pointing to the need to understand both the structure of the social space within which careers unfold and the complexity of condition, since both change over time. SCrT suggests that the measurement of career success requires pattern and narrative analysis rather than single-index measures.
Keywords: Z; 330; Berufserfolg - Konzeption; Berufsverlauf; berufliche Mobilität; Stellung im Beruf; Einkommen; Selbstverständnis; Berufszufriedenheit; Arbeitszufriedenheit; Biografieforschung; Mobilitätsforschung; sozialer Raum